Correlation between Hemoglobin Concentration and Oxygen Saturation Post-Exercise with Cardiorespiratory Fitness: Early Indicators for Cardiovascular Health in Young Adults - Elizabeth, Elizabeth; Haryono, Ignatio Rika; Prastowo, Nawanto Agung; Santosa, Mariani; Arrang, Sherly Tandi (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Cardiorespiratory fitness (CRF) is an important indicator of cardiorespiratory health and a strong predictor of mortality. Several factors affect CRF, including arterial oxygen content (CaO2), which is influenced by hemoglobin (Hb) concentration and oxygen saturation. However, the correlation between CRF and Hb remains inconclusive. This study aimed to explore the correlation between Hb concentration and oxygen saturation post-exercise with CRF, especially in young adults.Methods: A cross-sectional study was conducted in October 2024, involving 68 medical students from a university in Jakarta, Indonesia. Consecutive stratified sampling was applied based on gender. The Global Physical Activity Questionnaire (GPAQ) and the Physical Activity Readiness Questionnaire (PAR-Q+) were used as screening tools. Hb concentration and oxygens saturation were measured using a digital hemoglobinometer and pulse oximetry, while CRF was evaluated using a 20-meter multistage test. Additional measurements included body mass index (BMI), blood pressure, and heart rate. Data were analyzed with correlation and multiple linear regression tests.Results: The most participants were female (57.4%). Normal Hb concentration was found in 80.9% with mean Hb levels of 14.15±1.54 g/dL in males and 12.9±1.37 g/dL in females. CRF correlated positively with Hb concentration (p=0.005; r=1.13), and negatively with oxygen saturation post-exercise (p=0.005; r=-0.4). These correlations were significant in males and not in females. Conclusion: Hb concentration and oxygen saturation post-exercise significantly correlate with CRF in males, whereas BMI and physical activity play stronger roles in females. Maintaining optimal Hb levels, preventing anemia, and promoting active lifestyles are essential strategies to support CRF, cardiovascular health, and long-term wellness.